Mars Under Primordial Solar Wind Conditions: Mars Express Observations of the Strongest CME Detected at Mars Under Solar Cycle #24 and its Impact on Atmospheric Ion Escape. Issue 21 (4th November 2017) - Ramstad, Robin; Barabash, Stas; Futaana, Yoshifumi; Yamauchi, Masatoshi; Nilsson, Hans; Holmström, Mats
Abstract: An extremely strong Coronal Mass Ejection (CME) impacted Mars on 12 July 2011, while the Mars Express spacecraft was present inside the nightside ionosphere. Estimated solar wind density and speed during the event are 39 particles cm −3 and 730 km/s, corresponding to nominal solar wind flux at Mars when the solar system was ∼1.1 Ga old. Comparing with expected average atmospheric heavy ion fluxes under similar XUV conditions, the CME impact is found to have no significant effect on the escape rate 3.3 × 10 24 s −1, with an upper limit at 10 25 s −1 if the observed tail contraction is not taken into account. On the subsequent orbit, 7 h later after magnetosphere response, fluxes were only 2.4% of average. As such, even under primordial solar wind conditions we are unable to find support for a strong solar wind‐driven ion escape, rather the main effect appears to be acceleration of the escaping ions by ×10–×20 typical characteristic energy. Key Points: CME impacts Mars, upstream flux equivalent to nominal solar wind in the 1.1 Ga old Solar system; magnetosphere compressed to 1/4 tail area Impact enhances heavy ion fluxes in the tail by ×3 and accelerates the ions to ×21 higher energies, escape rate unchanged Upstream conditions sustained on next orbit though downtail escape fluxes only 2.4% of nominal with ×16 enhancement in energy